Flexible but Parsimonious Demand Designs: The Case of Gasoline - Coppejans, Mark (The Review of Economics and Statistics, 2003)
We consider expectations of the form E[logy|x] = Σj=1d αj log xj as a good starting point for a more general analysis. We show why this naturally leads to the following flexible functional form: E[y|x] = f(Σj=1dhj(xj)), where f(ċ) and the hj(ċ)'s are estimated by cubic splines. The main objective of this paper is to provide a straightforward method to estimate E[y|x]. We demonstrate the usefulness of this approach by estimating gasoline demand from the 1994 RTECS data set, and in doing so, uncover interesting relationships of income and age to expected gasoline use.